(untitled) (Hydro Nepal: Journal of Water, Energy and Environment, 2008)
Dams, environment and local people are interrelated. Large dams have several large scale advantages in irrigation, flood control, power generation, inland navigation etc. It is equally true that it has also many large scale adverse impacts inducing controversy and disputes. For example, despite enormous benefits to Canada from large scale dams, the local people of the Basin are still feeling deep resentment at the way they were treated. Hence, it is utmost necessary to thoroughly examine all the important aspects of the project particularly the environment side regarding the implementation of large dams. Hydro Nepal: Journal of Water, Energy and Envorinment Vol. 1, No. 2(2008) pp. 19-21